2018
DOI: 10.3892/mmr.2018.8945
|View full text |Cite
|
Sign up to set email alerts
|

Anesthetic effects of isoflurane and the molecular mechanism underlying isoflurane‑inhibited aggressiveness of hepatic carcinoma

Abstract: Anesthesia is produced by drugs or other methods, and refers to the attenuation of pain via reversible suppression of neuronal transmission in the central and peripheral nervous systems, during surgery. Clinical investigations have indicated that the anesthetic action of isoflurane is efficient to alleviate pain during tumor resection clinical trials. In addition, it has been reported that isoflurane can induce caspase-3 activation and is associated with apoptosis of tumor cells. The present study investigated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 40 publications
0
21
0
1
Order By: Relevance
“…To elucidate the underlying mechanism, we examined the effects of sevoflurane on AKT isoforms, which were reported to be involved in major cellular processes [17][18][19][20][21][22][23][24][25][26][27][28]. The overexpression of AKT isoforms in different types of malignancies is well documented [51].…”
Section: Discussionmentioning
confidence: 99%
“…To elucidate the underlying mechanism, we examined the effects of sevoflurane on AKT isoforms, which were reported to be involved in major cellular processes [17][18][19][20][21][22][23][24][25][26][27][28]. The overexpression of AKT isoforms in different types of malignancies is well documented [51].…”
Section: Discussionmentioning
confidence: 99%
“…Isoflurane is a volatile general anesthetic that can be used to induce and maintain general anesthesia to eliminate behavioral response in patients undergoing tumor resection. 39 A survival investigation indicated that the use of isoflurane or desflurane alone during glioblastoma surgery did not affect overall survival (OS) or progression-free survival (PFS) at 1 or 5 years. 5 Postoperatively, the plasma levels of IL-6 and IL-10 in 35 patients with colorectal cancer after surgery treated with isoflurane were significantly higher than baseline values before surgery.…”
Section: Isoflurane and Cancer The Impact Of Isoflurane On Clinical Omentioning
confidence: 99%
“…Isoflurane inhibited cell proliferation and reduced cell viability in HCC. 39 Furthermore, migration and invasion abilities of liver cancer cells were inhibited by isoflurane by attenuating nuclear factor-kappaB (NF-κB) activity. 39 These results uncovered that isoflurane plays an inhibitory role in liver oncogenesis (Table 2, Figure 3).…”
Section: The Biological Function Of Isoflurane In Suppressing Oncogenmentioning
confidence: 99%
See 2 more Smart Citations